Pelaksanaan Program Tahfidz Juz 30 Melalui Metode FALTORCAMA di MI Salafiyah Syafi’iyah Proto 01 Kedungwuni Pekalongan - Aan Fadia Annur; Syafa'atul Khusna; Latifah Amalia Fajarsiwi; Abidurrohman (Jurnal Riset Madrasah Ibtidaiyah, 2022)
The curriculum in the world of education continues to develop. At the Madrasah Ibtidaiyah level, curriculum development is carried out by holding a tahfidz program. MI Salafiyah Syafi'iyah (MISS) Proto 01 has a special method for implementing the tahfizh juz 30 program called the FALTORCAMA method. This study aims to explain the planning, implementation, and methods, as well as the inhibiting and supporting factors in the implementation of the tahfidz Juz 30 program through the FALTORCAMA method at MISS Proto 01 Kedungwuni Pekalongan. The method used in this study is a qualitative method with a descriptive approach, in seeking information about this research, the authors use interviews, observation, and documentation. The result of this research is that the planning of this program is based on efforts to increase students' abilities according to the conditions and potentials in their environment and as a form of the school's contribution to the surrounding community, namely realizing Proto Village as